CLINICAL EXPERIENCE OF NEXAVAR (SORAFENIB) APPLICATION IN PATIENTS WITH METASTATIC DIFFERENTIATED THYROID CANCER RESISTANT TO THERAPY 131I - P. A. Isaev; P. O. Rumyantsev; V. V. Polkin; A. A. Ilyin; D. Yu. Syomin; T. A. Agababyan; S. V. Vasilkov; V. S. Medvedev (Опухоли головы и шеи)
The treatment choice of differentiated thyroid cancer resistant to therapy 131I to be restricted just to systemic methods. Traditional chemotherapy demonstrated no clinically relevant effectiveness but high toxicity. With the introduction into clinical practice of multi-kinase inhibitor was able to significantly improve treatment outcomes.The paper demonstrated two patients with the incurable of differentiated thyroid cancer resistant to therapy 131I. All patients received Nexavar (sorafenib). Its therapeutic effectiveness varied from partial response to long-term stabilization.